Youth as a Subject and Object of State Youth Policy: Problematic Aspects of the Concept - I. S. Alekhina (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
The article discusses the concept of «youth», «youth policy» through the prism of historical, socio-political and legislative aspects of state youth policy in the Russian Federation. The authors analyzed the constitutions of the RSFSR and the USSR for the purpose of determining in them the concepts of the constitutional legal status of youth, as well as the constitution and legislation of the CIS member states, model legislative acts of the IPA CIS. As a result of the research of regulatory legal acts and specialized literature in the area of state youth policy, general patterns and legal uncertainties were identified: in terms of categorical-conceptual apparatus (for example, the lack of a definition of the term “teenager”), the age limits of youth, and problematic aspects of youth policy, an attempt was made to formulate development vectors and ways of addressing them.